Madrasah Public Relations Management in Attracting Public Interest - Ja'far, Ja’far (Nidhomiyyah: Jurnal Manajemen Pendidikan Islam, 2025)
Public relations (PR) is a critical aspect of educational institutions. This study aims to understand PR management and employs a qualitative method with a descriptive approach. The research findings reveal the PR strategies at MTs Al-Yasini, which include periodic work meetings between the principal and teachers concerning PR programs, providing optimal services to parents to attract public interest, and student presentations that captivate community interest. The challenges faced by the PR team at MTs Al-Yasini include the lack of parental concern for students’ and school-related issues. The school has taken measures to address these challenges by adopting a transparent approach, particularly in financial matters. Additionally, the school involves parents in discussions and decision-making processes related to school program planning. The school believes that such efforts will foster a sense of ownership among parents, as they feel valued as part of the school community. This study significantly contributes to our understanding of PR management in attracting public interest, particularly concerning strategies, activities, challenges, and solutions in PR practices.